2016
DOI: 10.1007/s12253-016-0114-1
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Contribution of Cox-2 Expression in the Progression of Oral Squamous Cell Carcinoma and H-Ras Activation

Abstract: The aim of this study was to investigate the relationship between the H-ras and Cox-2 gene expression in tumors from Iranian Oral Squamous Cell Carcinoma (OSCC) patients. Fresh tumor biopsies removed from oral cavity were collected from 67 new cases. Total RNA was extracted from biopsies and processed for quantification of H-ras and Cox-2 specific RNA expression using real-time PCR (QPCR). In addition, 59 gingival biopsies from apparently normal individuals were processed for QPCR assays. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…(It is the third most common malignancy in south-east Asia.) (2,6) Results: All grades of OSCC showed membranous immunosignaling of CD44. The well, moderately and poorly differentiated OSCC cases showed weak, moderate and intense positive membranous immunosignaling of CD44 respectively.…”
Section: Oral Squamous Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…(It is the third most common malignancy in south-east Asia.) (2,6) Results: All grades of OSCC showed membranous immunosignaling of CD44. The well, moderately and poorly differentiated OSCC cases showed weak, moderate and intense positive membranous immunosignaling of CD44 respectively.…”
Section: Oral Squamous Cell Carcinomamentioning
confidence: 99%
“…(1) Head and neck squamous cell carcinoma (HNSCC) is one of the most common malignancy in humans and one of the most common malignant tumors of the oral and maxillofacial regions. (2) In 2008; 263,900 new cases of head and neck cancer were diagnosed and 128,000 deaths related to this malignancy have occurred worldwide. (1) Estimation reveals that 11 out of every 100,000 adults diagnosed every year with oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of regional and distant metastases is favored by the capacity of tumors to progress locally, which subsequently invade lymphatic and blood vessels, and promote neo-angiogenesis. Morita et al showed that COX-2 promotes tumor lymphangiogenesis and lymph node metastasis in oral squamous cell carcinoma [25]. In their study, they showed a positive correlation of COX-2 expression to VEGF-C expression, a potent stimulator of lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 91%
“…The relative Real Time PCR, quantifying the cDNA levels of the gene of interest in relation to the normalizer (housekeeping) gene, possesses high sensitivity and specificity. The relative Real Time PCR is a key method for analyzing the relative expressional changes exhibited by the gene(s) of interest during cancer initiation, progression and metastasis . GAPDH has been used as the normalizer gene in relative Real Time PCR analysis with OSCC lesions …”
Section: Introductionmentioning
confidence: 99%
“…The relative Real Time PCR is a key method for analyzing the relative expressional changes exhibited by the gene(s) of interest during cancer initiation, progression and metastasis. [44][45][46] GAPDH has been used as the normalizer gene in relative Real Time PCR analysis with OSCC lesions. [47][48][49][50] The given case study centers on the young (36 years, female) early stage diagnosed OSCC case lacking addictive proclivities for tobacco, betel nut, and alcohol.…”
Section: Introductionmentioning
confidence: 99%